2015
DOI: 10.3390/ijms16036217
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Acylpeptide Hydrolase Bound to Chlorpyrifosmethyl Oxon and Dichlorvos

Abstract: Acylpeptide hydrolases (APHs) catalyze the removal of N-acylated amino acids from blocked peptides. Like other prolyloligopeptidase (POP) family members, APHs are believed to be important targets for drug design. To date, the binding pose of organophosphorus (OP) compounds of APH, as well as the different OP compounds binding and inducing conformational changes in two domains, namely, α/β hydrolase and β-propeller, remain poorly understood. We report a computational study of APH bound to chlorpyrifosmethyl oxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…N(omega)-ADP-D-ribosyl)-L-arginine) was downloaded from the Chemspider database and used in Gaussian 09 software at the B3LYP 6–31 G* set. 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N(omega)-ADP-D-ribosyl)-L-arginine) was downloaded from the Chemspider database and used in Gaussian 09 software at the B3LYP 6–31 G* set. 25 …”
Section: Resultsmentioning
confidence: 99%
“…2528 Solvation effects were evaluated by single-point calculations on the optimized geometries at the B3LYP 6–31G* level of theory as the geometry optimizations using the conductor-like polarized continuum model (C-PCM). 28 In the calculations, ε = 4 was used for the surrounding solvent.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a docking study was conducted to compare the binding mode and energy of trametinib to the ATP pocket and allosteric site of MEK1. As a result, the ligand (trametinib) was docked by AutoDock 4.2 [28,29]. The lowest conformations of MEK1-trametinib complex were selected for further docking analysis ( Figure 1C,D).…”
Section: Binding Mode Of Trametinib To Mek1mentioning
confidence: 99%
“…The electrostatic potential (ESP) on the molecular vdW surface was calculated to investigate and predict intermolecular interactions. The result demonstrated that the strength and orientation of weak interactions, including H bonds and halogen bonds, can be predicted and explained by analyzing the magnitude and positions of the minima and maxima on the surface [ 48 ]. The ESP-mapped vdW surface and the surface extrema of the three ligands are shown in Fig 3A and 3C and 3E ), and the surface areas of the ligands in their different ESP ranges are shown in Fig 3B, 3D and 3F ).…”
Section: Resultsmentioning
confidence: 99%